Hubungan Harga Diri Dengan Stres Kerja Pada Perawat Rumah Sakit PKU Muhammadiyah Surakarta - Soraya Husin, Lauditta, Achmad Dwityanto, S.Psi, M.Si (2017)
Self-esteem is one of the elements forming the personality that determines how individual against himself, how the individual in building relationships with other people and how people deal with the environment encountered when these capabilities can be achieved, individuals with positive self-esteem will be easy to adjust themselves and were able to solve the problems in the work so that it can suppress the emergence of stress at work, known as the stress of work. The purpose of this research is (1) to determine the relationship between self-esteem and the stress of work, (2) determine the level of self-esteem in hospital nurses. PKU Muhammadiyah Surakarta, (3) determine the level of job stress in nurses in RS PKU Muhammadiyah Surakarta, (4) determine the effective contribution of the dignity of work stress. Subjects in this study is the nurse at the Hospital of PKU Muhammadiyah Surakarta totaling 100 subjects. The sampling technique used is purposive sampling. Analysis of the data used in this research is using product moment correlation. The correlation between self-esteem with the stress of work is equal to -0.391, p = 0.000 (p <0.01), which means there is a significant negative relationship between self-esteem and job stress. The effective contribution of the dignity of work stress is 15.2%, this means that there are 84.8% of other variables that affect the stress of work such as social support, locus of control, flexibility and ability of the individual. Keywords: Self-Esteem, Job Stress